The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Drug Information and Pharmacotherapy 2017
DOI: 10.1136/ejhpharm-2017-000640.327
|View full text |Cite
|
Sign up to set email alerts
|

DI-080 Study of the use of canakinumab in muckle–wells syndrome in a tertiary hospital

Abstract: BackgroundCanakinumab is a IgG1 anti-interleukin-1β monoclonal antibody indicated in the treatment of Muckle–Wells syndrome (MWS). It is an autosomal dominant congenital disease that is considered a rare disease. Hives, joint pains, conjunctivitis, deafness, amyloidosis and fever are its symptoms. For years, the only available treatments were non-steroidal anti-inflammatory drugs (NSAIDs) and systemic corticoids.PurposeThe objective of this study was to determine the effectiveness of canakinumab in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ten observational studies reported the effectiveness of canakinumab in patients with different CAPS phenotypes and of various age groups. 34 3941 48 52 59 66 82 92 Among the studies reporting CR/PR, 93% of canakinumab-treated MWS patients achieved a CR at short-term follow-up. 59 Patients who achieved a CR with canakinumab ranged from 62% 48 to 93% 59 at mid-term follow-up, and 50% 34 52 to 100% 82 at long-term follow-up (online supplementary figure 2A–B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten observational studies reported the effectiveness of canakinumab in patients with different CAPS phenotypes and of various age groups. 34 3941 48 52 59 66 82 92 Among the studies reporting CR/PR, 93% of canakinumab-treated MWS patients achieved a CR at short-term follow-up. 59 Patients who achieved a CR with canakinumab ranged from 62% 48 to 93% 59 at mid-term follow-up, and 50% 34 52 to 100% 82 at long-term follow-up (online supplementary figure 2A–B).…”
Section: Resultsmentioning
confidence: 99%
“…34 3941 48 52 59 66 82 92 Among the studies reporting CR/PR, 93% of canakinumab-treated MWS patients achieved a CR at short-term follow-up. 59 Patients who achieved a CR with canakinumab ranged from 62% 48 to 93% 59 at mid-term follow-up, and 50% 34 52 to 100% 82 at long-term follow-up (online supplementary figure 2A–B). Other observational studies have also shown the effectiveness of canakinumab in improving the Disease Activity Score (DAS), 57 65 Autoinflammatory Disease Activity Index (AIDAI) score, 36 83 complete/partial resolution of symptoms, 38 45 88 improvement in physician/patient assessed PROs 36 65 85 and the Child Health Assessment Questionnaire (CHAQ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation